Hazard Risk Management Analysis PO PT Gunung Harta Transport Solutions Uses FMEA And RCA Methods - Kadek Bintang Wigayana; Rifano (Universitas Medan Area, 2025)
This study aims to determine the potential hazards and risks and to find the root causes of potential hazards and risks in the public transportastion company PT. Gunung Harta Transport Solutions. The methods used are FMEA and RCA with an observation, interview, questionnaire, and documentation approach. The research sample is the Head of Office Administration, Head of Workshop, and Head of Operational Staff. The results of the assessment of 32 indicators using the FMEA method, obtained RPN values with codes X1 to X32. Of the 32 indicators included in the ranking category, 2 are Critical, 3 are High, 7 are Medium, and 20 are Low. To find potential causes of danger, using the RCA method from the RPN results. The office section is the use of computers/laptops, office staff work beyond office operating hours and lack of rest breaks for office staff. The workshop section is the repair of the AC system, lack of awareness of the importance of implementing K3 in the workshop. The operational section is reckless drivers, lack of driver understanding regarding driving safety. This study concludes that companies must always pay attention to K3 aspects in every office, workshop, and vehicle operation activity.